2019
DOI: 10.1002/ecy.2570
|View full text |Cite
|
Sign up to set email alerts
|

Consumer trophic positions respond variably to seasonally fluctuating environments

Abstract: The effects of environmental seasonality on food web structure have been notoriously understudied in empirical ecology. Here, we focus on seasonal changes in one key attribute of a food web, consumer trophic position. We ask whether fishes inhabiting tropical river–floodplain ecosystems behave as seasonal omnivores, by shifting their trophic positions in relation to the annual flood pulse, or whether they feed at the same trophic position all year, as much empirical work implicitly assumes. Using dietary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…() and McMeans et al. () as well as unpublished stable isotope data for the Tonle Sap system. Lastly, site‐level species abundances were plotted across the nine sites to explore species patterns from the exterior to the interior of the floodplain during the wet season.…”
Section: Methodsmentioning
confidence: 92%
“…() and McMeans et al. () as well as unpublished stable isotope data for the Tonle Sap system. Lastly, site‐level species abundances were plotted across the nine sites to explore species patterns from the exterior to the interior of the floodplain during the wet season.…”
Section: Methodsmentioning
confidence: 92%
“…release eggs just before or during the flood season, which allows them to migrate into the floodplain and escape predation, whereas in the dry season, the isolated water bodies in the floodplain provide shelter for them (Bayley & Li, ; Junk, Soares, & Saint‐Paul, ; Welcomme, ). Furthermore, a recent finding suggested that fish species respond to the flood pulse differently as revealed by the dietary (stomach contents) and nitrogen stable isotope ( 15 N) analysis in the fish sampled from TSL (McMeans et al, ). Although the results of this study can now provide quantitative descriptions of connectivity among hydrological elements related to fish habitat assemblage, further studies should quantitatively investigate the relationship between fish production and inundation patterns in this kind of fluctuating water environment influenced by flood pulses.…”
Section: Discussionmentioning
confidence: 99%
“…This citizen‐science reporting and observer network is complemented by a series of other survey techniques, used in combination and applied at set locations (Elliott et al, ; Gotzek & Johnson, ). Targeted ecological surveys to determine population distribution (Kong et al , ; Elliott & Chheng, ), identify spawning site locations (Elliott & Chheng, ), evaluate food‐web ecology (McMeans et al, ; Pool et al, ) and for population genetic analysis (Elliott & Uy, ), using traditional standardised nets are seasonally implemented at set locations. Both qualitative and quantitative market surveys are used to determine commercial fishing pressure (Gotzek & Johnson, ).…”
Section: Application To the Complex Lower Mekong Basin Multi‐species mentioning
confidence: 99%
“…This citizen-science reporting and observer network is complemented by a series of other survey techniques, used in combination and applied at set locations Gotzek & Johnson, 2019). Targeted ecological surveys to determine population distribution (Kong et al, 2017;, identify spawning site locations , evaluate food-web ecology (McMeans et al, 2019;Pool et al, 2017) and for population genetic analysis FiA, 2018a;Gotzek & Johnson, 2019). To contextualise fisher catch data, to obtain estimates of consumption and to provide an independent estimate of the subsistence fishery, household surveys have also been conducted by the fisheries administration (IFReDI, 2013).…”
Section: Application To the Complex Lower Mekong Basin Multi-speciementioning
confidence: 99%